Biosynthesis of Zinc Oxide Nanoparticles for Corrosion Protection Application - Md Akhir, Rabiatuladawiyah; Haziq Norashikin, Mohamad; Muzamir Mahat, Mohd; Najmi Bonnia, Noor (International Journal of Engineering and Technology, 2019)
The present study reports the successful synthesis of biosynthesized zinc oxide nanoparticles (ZnONPs). The Pandanus Amaryllifolius leaves extract was used as reducing agent with zinc nitrate hexahydrate as precursor. The effects of synthesis temperature on biosynthesis of ZnONP’s are discussed.  The biosynthesized ZnONPs were characterized by X-ray diffraction (XRD) ; and they were found to exhibit the hexagonal wurtzite structure. The diffractograms revealed well-defined, strong and sharp peaks at 2θ positions that correspond to its crystallinity with average size of 16.25 nm. Micrograph images from Field Emission Scanning Electron Microscope (FESEM) have shown polydispersed spherical shape of the biosynthesized ZnONPs. Smaller grain sizes were produced at low synthesis temperature of 60ºC. The elemental composition analysis confirmed the presence of zinc and oxygen by Energy Dispersive X-ray (EDX). The corrosion inhibition efficiency of mild steel in 1.0 M hydrochloric acid (HCl) solution was determined by weight loss method. Of significance, good corrosion inhibition efficiency of 79.43% was obtained by incorporating the biosynthesized ZnONP’s at synthesis temperature of 60ºC.